Novel topical therapy for mild-to-moderate plaque psoriasis: focus on calcitriol - Lutz Kowalzick (Clinical, Cosmetic and Investigational Dermatology, 2009)
Lutz KowalzickDepartment of Dermatology and Allergology, HELIOS Vogtland-Klinikum Plauen GmbH Plauen, GermanyAbstract: The benefits of vitamin D derivatives for the treatment of chronic plaque psoriasis are well documented. Of importance is how compatible they are with, and how they compare to, other established treatments for psoriasis. This paper reviews 15 studies with calcitriol 3 µg g-1 ointment (Silkis®/Vectical™ ointment; Galderma Laboratories) applied twice daily for up to 52 weeks. The ointment was found to be effective and safe for the treatment of mild-to-moderate plaque psoriasis including sensitive skin areas. Calcitriol 3 µg g-1 ointment was found to be as effective as, or even superior to, other established treatment modalities and more highly tolerated than other local treatment modalities in most studies’ comparisons. It could be combined with other psoriasis treatment modalities such as ultraviolet B phototherapy or topical corticosteroids in order to achieve a faster response and in order to reduce the risk of adverse events.Keywords: 1,25-dihydroxyvitamin D3, calcitriol, psoriasis, therapy